4,887 views

Let $a(x, y), b(x, y,)$ and $c(x, y)$ be three statements with variables $x$ and $y$ chosen from some universe. Consider the following statement:

$\qquad(\exists x)(\forall y)[(a(x, y) \wedge b(x, y)) \wedge \neg c(x, y)]$

Which one of the following is its equivalent?

1. $(\forall x)(\exists y)[(a(x, y) \vee b(x, y)) \to c(x, y)]$
2. $(\exists x)(\forall y)[(a(x, y) \vee b(x, y)) \wedge\neg c(x, y)]$
3. $\neg (\forall x)(\exists y)[(a(x, y) \wedge b(x, y)) \to c(x, y)]$
4. $\neg (\forall x)(\exists y)[(a(x, y) \vee b(x, y)) \to c(x, y)]$

$(\exists x)(\forall y)[(a(x, y) \wedge b(x, y)) \wedge ¬c(x, y)]$

$\quad \equiv ¬(\forall x)¬(\forall y)[(a(x, y) \wedge b(x, y)) \wedge ¬c(x, y)]$
$\quad (\because (\exists x) F(x) = \neg \forall x \neg F(x))$

$\quad \equiv ¬(\forall x)(\exists y)¬[(a(x, y) \wedge b(x, y)) \wedge ¬c(x, y)]$
$\quad (\because (\forall x) F(x) = \neg \exists x \neg F(x)), \neg \neg F(x) = F(x))$

$\quad \equiv ¬(\forall x)(\exists y)[¬(a(x, y) \wedge b(x, y)) \vee c(x, y)]$

$\quad \equiv ¬(\forall x)(\exists y)[(a(x, y) \wedge b(x, y)) → c(x, y)]$

(C) choice.

by

@Arnab , ¬∀x¬f(x) = ∃x¬¬f(x) = ∃xf(x)(because by demorgan's law we are getting this)

srestha

what is now not in syllabus??

edited by

@akash

I thought it is logic programming

sorry misunderstood

1
2
11,650 views
3
9,975 views